Advanced aging effects on implicit motor imagery and its links to motor performance: An investigation via mental rotation of letters, hands, and feet - Muto, Hiroyuki; Suzuki, Maki; Sekiyama, Kaoru (Frontiers in Aging Neuroscience, 2022)
This study focuses on changes in implicit motor imagery during advanced aging and these changes’ co-occurrences with physical motor deficits. We administered a mental rotation (MR) task with letters, hands, and feet to 28 young adults (20–27 years) and to 71 older adults (60–87 years), and assessed motor skills (gait mobility and hand dexterity) and neuropsychological performance. Compared to young adults, older adults showed lower MR performance for all stimuli and stronger biomechanical constraint effects on both hand and foot rotation. Moreover, the foot biomechanical constraint effect continued to increase during late adulthood, and declines in hand and foot motor imagery emerged at earlier old ages than declines in visual imagery. These results first demonstrated distinct aging trajectories of hand motor imagery, foot motor imagery, and visual imagery. Exploratory partial correlation analysis for older adults showed positive associations of low-level perceptual-motor skills (Trail Making Test-A performance) with hand and foot MR performance and positive associations of mobility (Timed Up and Go test performance) with foot and letter MR performance. These associations exhibited somewhat different patterns from those of young adults and raised the possibility that age-related declines in motor (and visual) imagery co-occur with declines in motor functioning.